Indacaterol 75 µg once daily for the treatment of patients with chronic obstructive pulmonary disease: a North American perspective - Edward M. Kerwin; James Williams (Therapeutic Advances in Respiratory Disease, 2013)
Chronic obstructive pulmonary disease (COPD) is a progressive disease in which patients become increasingly disabled by their symptoms and limited in their activities. Health-related quality of life may be profoundly impaired even in the early stages of the disease. Treatment with long-acting inhaled bronchodilators can improve lung function, symptoms and health status and reduce exacerbations of COPD. This review profiles the efficacy, safety and tolerability of indacaterol, an inhaled β 2 -agonist bronchodilator for once-daily maintenance treatment of patients with COPD. After 12 weeks of treatment with a once-daily dose of 75 µg (the dose approved in the USA and Canada) in patients with moderate to severe COPD, compared with placebo, indacaterol provided significant and clinically relevant levels of bronchodilation [difference in trough forced expiratory volume in 1 s: 131 ml; 95% confidence interval (CI) 104–159; p < 0.001], together with significant reductions in symptom scores (difference in transition dyspnea index total score: 0.84 points; 95% CI 0.37–1.31; p < 0.001) and improvements in health status (difference in St George’s Respiratory Questionnaire total score: −3.8 units; 95% CI −5.6 to −2.0; p < 0.001). The overall safety and tolerability of once-daily treatment with indacaterol 75 µg for 12 weeks did not differ in any substantial aspect from placebo treatment. Indirect comparisons analyzing pooled clinical data and meta-analyses suggest that treatment with indacaterol 75 µg once daily may be effective in reducing exacerbations of COPD, and that its effects on lung function and health status will be comparable with other currently available inhaled long-acting bronchodilators used for COPD. Treatment with indacaterol 75 µg once daily provides effective bronchodilation, improves dyspnea and health status, and has a well characterized profile of safety and tolerability.